قياس العلاقـــة الدّيناميكيّــــة بين الصّدمـــات الاقتصاديّة وأداء البورصات العربيّة (Revue El-Wahat pour les Recherches et les Etudes, 2020)
This paper aims to measurement and analysis the effects that economic shocks can leave represented in the oil price, exchange rate against the US dollar, money supply and interest rate on the Arab stock exchanges for the period from 2007-2017, This study includes Saudi stock market index TADAWUL, ADSMI and DSM-200, Using monthly data for stock indices and economic variables, We apply GARCH models, and The Error Correction Model (ECM), We conclude that there is a cointegration between economic variables and the volatility of returns, The existence of a long-term equilibrium relationship tends from economic variables to volatilities, There is a volatility Saudi stock market is Mainly related to the exchange rate variable, and interest rate in the Abu Dhabi stock markets, and oil price in the Qatar Exchange. Keywords-Co-Integration, Demand Shocks, Supply Shocks, Error Correction Model, Arab stock exchanges.